The benefits of component-resolved diagnosis in diagnostics of peanut allergy - Choina, Magdalena; Gromek, Weronika; Marzęda, Magdalena; Lishchuk-Yakymovych, Khrystyna; Majsiak, Emilia (Journal of Education, Health and Sport, 2022)
Introduction: Why can a peanut allergy cause exceptionally severe reactions, but not to everyone? Is there a way to identify patients who might experience these reactions? What is molecular diagnostics of allergy and what are the benefits of diagnosing patients at risk of anaphylaxis after consuming peanuts? Purpose: The aim of the study is to show the benefits of molecular diagnostics of allergies based on the example of peanut allergy. Description of the state of knowledge: The diagnosis of peanut allergy is based on the assessment of the clinical presentation. The gold diagnostic standard is to perform a food challenge for suspected allergen. The following tests are helpful in diagnosis: skin tests or determination of allergen-specific E antibodies (asIgE) in blood serum. Until recently, the determination of asIgE concentration was possible only for allergen extracts. A milestone in diagnosing allergies is a serological diagnosis based on allergen molecules. The possibility of testing individual molecules increases the sensitivity and specificity of peanut allergy diagnostics and allows to indicate the risk of anaphylaxis in individual patients. Summary: Molecular diagnostics in individuals with peanut allergy make it possible to determine the individual patient’s allergy profile and indicate the risk of anaphylaxis. The information obtained with the help of this tool allows for precise therapeutic recommendations for people allergic to peanuts. Such diagnostics is a step towards personalized medicine in allergology. Keywords: allergy; molecular diagnostics of allergy; allergen-specific E antibodies; asIgE